Culture Shock and Maternal Anxiety During Pregnancy: A Review of Health System Responses in Low-Income Countries - Nuraisyah Bahar; Dewi Hestiani K; Andi Tenriola (Jurnal Life Birth, 2025)
Pregnancy is a crucial and unique period in a woman's life marked by significant physiological and psychological changes. One of the main challenges is maternal anxiety, especially when women must adapt to new norms, values, or health practices that differ from their cultural background, known as culture shock. This phenomenon is often experienced by pregnant migrants, minority groups, and women in low-income countries who undergo shifts in roles and traditions during pregnancy. This study aims to systematically review how health systems in low-income countries respond to culture shock and maternal anxiety during pregnancy. This research employed a systematic review design with a PRISMA approach. The sample consisted of 48 selected scientific articles, identified through screening, eligibility, and exclusion processes from an initial total of 513 articles obtained from Google Scholar, Scopus, and PubMed databases. The results reveal that culture shock among pregnant women manifests as confusion about new practices and rituals, value and norm conflicts, social isolation, language barriers, as well as stigma and social pressure. Maternal anxiety is influenced by physiological changes, lack of knowledge, social pressures, and cultural differences. Health system responses in low-income countries still face major challenges, but several effective strategies have been identified, such as integrating psychological interventions (CBT, mindfulness), involving communities and families, culturally-based education, and health worker training on cultural competence. In conclusion, culture shock is a major trigger for maternal anxiety during pregnancy and requires adaptive, culturally sensitive, and community-oriented health system responses to optimize maternal and infant health outcomes.